Application of Caputo fractional approach to MHD Casson nanofluid with alumina nanoparticles of various shape factors on an inclined quadratic translated plate - Mahitha, Orugonda; Avula Golla, Vijaya Kumar; Öztop, Hakan Fehmi; Bangalore, Rushi Kumar (Elsevier B.V., 2024)
The present study aims to examine the effect of convective heat transfer of nanofluid past an inclined plate. This paper scrutinizes heat transfer over an inclined surface of alumina nanofluids under the influence of radiation and magnetic fields with temperature-dependent thermophysical properties. The mathematical findings of velocity and temperature distributions are examined and visualized using non-dimensional flow parameters. The core of the research is to know the impact of using shape effects of alumina nanoparticles with a variety of base fluids like water, ethylene glycol, and engine oil. The outcomes concluded that the friction of the non-Newtonian viscous fluid decreased with increasing the inclination of the surface. The governing equations of the flow have been developed by using a few approximations such as Boussinesq's, and Roseland's. Using the dimensional analysis, the initial governing equations are simplified to dimensionless partial differential equations. A fractional model is developed using the Caputo fractional derivative. The solution of the proposed fractional partial differential equations is obtained in terms of special functions, Wright function, and Mittag-Leffler function by using the Laplace transformation method. Based on the interpretation, it is found that a reduction in velocity is observed with an increase in the angle of inclination i.e., ? = ?/3 to ? = ?/2. From the analysis, it is found that alumina/engine oil can carry higher temperatures than compared to other nanofluids and thus is a good option for heat transfer devices. © 2024 The Authors
Keywords: Alumina nanoparticles; Caputo fractional derivative; Inclined plate; Radiation; Shape effects; Wright function